Pengaruh Brand Image, dan Lapangan Pekerjaan Terhadap Keputusan Mahasiswa untuk Memilih Jurusan Akuntansi pada Perguruan Tinggi yang Ada di Bandar Lampung - Chairul Anwar; Fredi Budiman (Universitas Bandar Lampung (UBL), 2016)
Education is one of the most important priority for most people. Most of the people have hope to be able to continue and complete their education to the highest level. It is undeniable that the provision for the world of work is to have a higher education. But in the process to continue their education to a higher level will be faced with a variety of considerations, namely the quality of the brand image of the majors and jobs after completing education. This study demonstrated for the influence of brand image and employment of the decision to choose accounting majors at the College in Bandar Lampung. The analytical method used is multiple linear regression analysis partially by the number of respondents comprised 100 students from each of the 20 students from universities in the city of Lampung. Data collection techniques used in this research is through field studies, literature studies and questionnaires. Based on the results of the discussion can be concluded that partial denagn directly using the t test, it appears that the hypothesis testing results show the brand image t value amounted to 12.589> 1.661 t table with a level of significance 0.000 <0.05, which means that the hypothesis in this study refused Ho and accept Ha. It can be concluded that the